Tunable subwavelength terahertz plasmonic stub waveguide filters - Tao, Jin (2013)
Tunable subwavelength terahertz plasmonic stub waveguide filters based on indium antimonide are proposed and numerically investigated. The transmission line theory and the Finite Different Time Domain simulation results reveal that the single-stub waveguide structure can realize a stop-band filtering function and the central wavelength of the notch is linearly dependent on the stub length while nonlinearly dependent on the stub width. The central wavelength of the notch can be actively controlled by tuning the temperature. The proposed filters may have applications in THz highly-integrated plasmonic circuits.